New sights on the associations between the XRCC1 gene polymorphisms and hepatocellular carcinoma susceptibility. Issue 2 (2nd September 2019) - Cai, Wenjuan; Liu, Xinhua; Li, Yan; Bi, Bowen; Liu, Lei; Wang, Zhenglu
Abstract: Studies investigating the relationships between the polymorphisms in the X‐ray repair cross complementing 1 ( XRCC1 ) gene and the susceptibility of hepatocellular carcinoma (HCC) remained controversial, therefore, we assessed this associations by metaanalysis and trial sequential analysis (TSA). PubMed, Embase, Google Scholar, Chinese National Knowledge Infrastructure and Baidu Scholar were comprehensively screened to retrieve relevant studies up to May 20, 2019. A total of 32 studies was included. Significant associations were discovered in the overall and subgroup analysis in these three polymorphisms. Interestingly, the decreased risk of HCC was detected in the Indians for the rs24587 polymorphism. TSA indicated the required information size for the rs25487 polymorphism were reached, but for the rs25489 and rs1799782 polymorphisms, more well‐designed trials were required. Sensitivity analysis implied our results were stable; no publication bias was observed in the rs25487 and rs1799782 polymorphisms. The bioinformatic analysis indicate that the rs1799782 polymorphism is probably damaging and has an influence on the XRCC1 protein function. Our study indicated that the XRCC1 rs25487 was a risk factor for the susceptibility of HCC, which was verified by the TSA. In addition, the rs25489 and rs1799782 polymorphisms were associated with increased risk of HCC. In the subgroup analysis, increased risks were detected in some subgroups (in accordance with Hardy‐Weinberg equilibrium, Chinese groups, Mongoloid subgroup, polymerase chain reaction‐restriction fragment length polymorphisms and more than 300 subgroups), moreover, decreased HCC risk of the rs25487 polymorphism was firstly observed, which required further studies to verify. Abstract : Our metaanalysis indicated that the X‐ray repair cross complementing 1 (XRCC1) rs25487, rs25489, and rs1799782 polymorphisms could increase the risk of HCC. Decreased HCC risk of the rs25487 polymorphism was firstly observed, which required further studies to verify.